Challenges in Securing Networked J2ME Applications. - Klingsheim, André N.; Moen, Vebjørn; Hole, Kjell J. (Computer (00189162), 2007)
The article discusses the Java 2 Micro Edition (J2ME) software that most of the currently marketed mobile smart phones support. The software faces the challenges of quality issues resulting from specific phones having their own bugs. This causes Java to maintain parallel versions of their source code to support as many devices as possible. There are also expected security problems with the software resulting from complex funtionality-rich security libraries. The article also shows how the J2ME technology is implemented on real devices and provides insights into the problems researchers encounter during the development process.